Bali to Plan Tourist Retribution in 2024 - Trisnawathi, Ida Ayu Adi (Bali Tourism Board, 2023)
There are intentions to enhance Local Revenue (PAD) in Bali Province. In recent years, tourism has emerged as a vital economic sector, contributing significantly to regional income. Local governments adept at managing tourist attractions stands a better chance of increasing local original revenue (PAD). In conclusion, the proposed introduction of a mandatory levy of IDR 150,000 per person for foreign tourists visiting Bali reflects the Bali Provincial Government's commitment to addressing budget deficits and enhancing local revenue. This initiative, aligned with Law No. 15 of 2023, aims to safeguard Bali's culture, natural environment, and infrastructure development. The funds collected are intended to support environmental conservation and waste management, contributing to the sustainability of Bali's tourism sector. The Bali Regional People's Representative Council (DPRD Bali) has taken steps to ensure transparency in fund management, emphasizing the mandatory nature of the levy and outlining sanctions for non-compliance. Tourism stakeholders, including the Bali Tourism Board, generally support the imposition of levies on foreign tourists, considering it a global practice. The success of this initiative depends on the careful management of funds, collaboration among stakeholders, and adherence to regulations. If implemented successfully, the levy has the potential to generate significant revenue, estimated at around IDR 900 billion per year if foreign tourist visits reach pre-pandemic levels. The ultimate goal is to utilize these funds for the development of Bali's tourism infrastructure, targeting premium and upper-middle-class international tourists while promoting sustainable tourism practices.